The Effectiveness of Digital Comics in Arabic Vocabulary Teaching - Muhammad Adhiem Bahri; Haeriyyah Haeriyyah; Yusring Sanusi Baso; Andi Aggussalim (Jurnal Al Bayan: Jurnal Jurusan Pendidikan Bahasa Arab)
This article discussed the role of technology in the learning process, especially in Arabic language teaching at MTsN 1 Makassar City. Teachers are faced with the challenge of improving students' ability to master vocabulary which conventional methods are often less interesting. This research proposes using visual media, such as digital comics, to make the learning process more interesting and effective. Digital comics are considered as media that can increase students' motivation and understanding and have been proven effective in increasing students' interest and understanding, especially in learning vocabulary. Research and Development (R&D) method was used in this research with the Four-D model which includes the stages of define, design, develop, and disseminate. This research was conducted at MTsN 1 Makassar City, with subjects consisting of two media experts, four material experts, and twenty-seven students of grades VII, VIII, and IX. The results showed that Arabic digital comics have a very good level of feasibility based on the responses of media experts, material experts, and students, with an average score percentage of 90.66% from the media aspect, 91.5% from the material aspect, and 78.07% from student responses. Visual media such as digital comics can attract students' interest, increase learning motivation, and help them understand Arabic vocabulary better. It is expected that this research can be a reference in developing innovative and effective language-learning media in the future.